Two predatory Medetera (Diptera: Dolichopodidae) species associated with Ips acuminatus (Gyllenhal) (Coleoptera: Curculionidae) in Bulgaria - Mihail Kechev; Sevdalin Belilov; Georgi Georgiev (Historia naturalis bulgarica, 2022)
In 2021 and 2022, two predatory flies from the genus Medetera (Diptera: Dolichopodidae) were recorded in galleries of Ips acuminatus (Coleoptera: Curculionidae) on Pinus sylvestris trees in Sredna Gora Mountain in Bulgaria: M. pinicola and M. dendrobaena. These findings appear to be the first associations with I. acuminatus. In addition, the first record of Medetera cf. dendrobaena for the fauna of Bulgaria was also recorded. As only a female specimen was found, the identification remains doubtful for the moment.